Rapport management in hotel responses to online reviews in Malaysia - Taw, Ly Wen (2021)
Digital technology has permitted an immense transformation in both modes and ease of communication. The development of web-based technologies such as the internet has increased the popularity of the marketing strategy of electronic Word-of-Mouth (eWOM) via online reviews, which have a major impact on consumers’ purchasing decisions. There has been growing use of social media in numerous industries, including the hotel industry, which has led to the prevalence of various websites with online hotel reviews. Follow-up customer service is an effective way to retain customer loyalty; therefore, responding to customers’ online reviews can establish rapport with existing customers, in addition to building a hotel’s brand reputation. Past studies have shown that online reviews have considerable influence on online hotel booking intentions in Malaysia. Despite the importance of management responses to customers’ online reviews, there remains a paucity of studies on hotel responses from a linguistic perspective. In particular, no previous study has investigated Malaysian hotel management’s language in responding to online reviews. Drawing upon Spencer-Oatey’s (2008) Rapport Management Model (RMM), this study investigates how Malaysian five-, four- and three-star hotels respond to online reviews on the well-known travel website, TripAdvisor. While previous studies focused on hotel responses to negative online reviews, this study explores the management’s rapport management strategies in RMM domains of illocutionary, discourse and stylistic in responding to both positive and negative reviews. Using purposeful sampling, the data of hotel responses from Malaysian five-, four- and three-star hotels were collected. These hotels are situated in tourist destinations in the capital city, Kuala Lumpur as well as the states of Selangor and Pahang. Drawing upon three different analytical frameworks based on the respective aforementioned domain, the linguistic phenomena were coded according to the domain and hotels’ star ratings in the responses using NVivo 12. The findings indicate that the five- and four-star hotels had higher frequencies of using expressing gratitude and apology strategies, moves occurrences and affective lexical resources in the responses to online reviews, compared with the three-star hotel management. It was also found that the five- and four-star hotels appeared to emphasise formality in language and writing styles to manage rapport via hotel responses, in addition to their use of varied lexical items to express emotions in creating digital emotional engagement. This study contributes to the understanding of hotel management practices in relation to online reviews in the specific sociocultural context of Malaysia. Further, the insights gained from this study may be of assistance in creating practical guidelines for the Malaysian tourism and hotel industries to enhance the effectiveness of virtual rapport building practices.